On the Question of Isostasy of the Okhotsk Region (K Voprosu ob Izostazii Okhotskogo Regiona) - Andreev,A. A. (1973)
The basic result of studies of isostatic conditions in the Okhotsk region is the establishment of the fact that conditons close to equilibrium exist in the water areas of the Sea of Okhotsk. As a consequence, the isostatic state of the Okhotsk region was studied on the basis of an analysis of the isostatic anomalies and of the approximate overcompensation coefficients, and also by estimating the vertical pressure in the mantle along deep seismic sounding profiles. In this article a method is given for the study of isostasy, which differs from all other preceeding methods. (Author) Technical trans. of Geologiya i Geofizika (USSR) n8 p1080 p108-112 1973, by H. Tomas.